Ethical Risks in Digital Behavior : Politics, Democracy and Citizenship - Guerrero-Lobo, José Francisco; Villalobos-Antúnez, José Vicente; Prats-Palma, Belisario (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Ethical risks in digital behaviour. Politics, democracy and citizenship Deliberative democracy deployed from phenomenology, from which it wants to return to things themselves as Martin Heidegger affirms is "to allow to see what is shown, as it is shown by itself, effectively by itself" (Heidegger, 2009, p. 45) we will find worlds where digital behaviour stimulates the ethical risks that affect politics, democracy and citizenship; and its implications in the mediations of citizens according to different understandings of the world of social networks with their contributions and effects.